2008
DOI: 10.1586/17474124.2.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgery-induced weight loss on immune function

Abstract: The biological mechanisms that link obesity to many forms of cancer seem to be multifactorial and involve a network of metabolic and immuno logical factors."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Moulin et al have recently shown that severely obese patients have a significantly lower natural killer (NK) cell cytotoxic activity as compared to normal individuals matched for age and gender, with lower defence against invaders such as precancerous and cancerous cells [112]. Interestingly, weight loss (26% less of initial weight) is responsible for an increase in NK cytotoxic activity after 6 months from gastric bypass surgery [112].…”
Section: Biological Mechanisms Linking Abdominal Obesity To Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Moulin et al have recently shown that severely obese patients have a significantly lower natural killer (NK) cell cytotoxic activity as compared to normal individuals matched for age and gender, with lower defence against invaders such as precancerous and cancerous cells [112]. Interestingly, weight loss (26% less of initial weight) is responsible for an increase in NK cytotoxic activity after 6 months from gastric bypass surgery [112].…”
Section: Biological Mechanisms Linking Abdominal Obesity To Cancermentioning
confidence: 99%
“…Moulin et al have recently shown that severely obese patients have a significantly lower natural killer (NK) cell cytotoxic activity as compared to normal individuals matched for age and gender, with lower defence against invaders such as precancerous and cancerous cells [112]. Interestingly, weight loss (26% less of initial weight) is responsible for an increase in NK cytotoxic activity after 6 months from gastric bypass surgery [112]. Lynch et al have recently shown that omental invariant NKT (iNKT) cell frequencies were lower in patients with severe obesity as compared to lean healthy subjects, thus suggesting a novel role for the omentum in immune regulation and tumor immunity [113].…”
Section: Biological Mechanisms Linking Abdominal Obesity To Cancermentioning
confidence: 99%
“…The underlying biological mechanisms still remain unclear, but there are several studies focusing on the link between obesity and cancer. Besides reduced insulin resistance [4], physical activity [5] and sex hormones [6], also the influence of obesity on immune functions is discussed [7]. Previous studies could show a central role of the adipocytokine leptin on the innate immune system [811].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, obese patients who lost body weight by bariatric surgery or by exercise training and nutrition courses could reverse their impaired NK cell activity and NK cell-mediated cytokine synthesis [7, 18]. This indicates that there might be a close interaction between impaired NK cell functions in obese individuals and the increased risk for cancer in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, levels of monocyte chemoattractant protein-1 and interferon gamma, which are important components of the immune response to infectious pathogens, were restored after weight loss induced by RYGB [12]. Furthermore, natural killer cell activity, innate immune cells involved in the control of cancer and infections, was enhanced after RYGB [13]. Recently, an inverse relationship between the change in certain T cells (CD4+ and CD3+) and the amount of weight lost after gastric bypass surgery has been noted [14].…”
Section: Case Presentationmentioning
confidence: 99%